Dietary compounds as potential modulators of microRNA expression in psoriasis - Hristina Kocic; Giovanni Damiani; Bojana Stamenkovic; Michael Tirant; Andrija Jovic; Danica Tiodorovic; Ketty Peris (SAGE Publishing, 2019)
Nutrigenomic DNA reprogramming in different chronic diseases and cancer has been assessed through the stimulation of gene expression and mRNA synthesis versus DNA silencing by CpG DNA modification (methylation); histone modification (acetylation, methylation) and expression of small noncoding RNAs, known as microRNAs (miRNAs). With regard to the specific nutrigenomic effects in psoriasis, the influence of specific diets on inflammatory cell signaling transcriptional factors such as nuclear factor (NF)-κB and Wnt signaling pathways, on disease-related specific cytokine expression, pro/antioxidant balance, keratinocyte proliferation/apoptosis and on proliferation/differentiation ratio have been documented; however, the influence of dietary compounds on the balance between 'good and bad' miRNA expression has not been considered. This review aims to summarize knowledge about aberrant microRNAs expression in psoriasis and to emphasize the potential impact of some dietary compounds on endogenous miRNA synthesis in experimental conditions in vivo and in vitro . Among the aberrantly expressed miRNAs in psoriasis, one of the most prominently upregulated seems to be miR-21. The beneficial effects of phenolic compounds (curcumin and resveratrol), vitamin D, methyl donors, and omega-3 fatty acids (eicosapentaenoic acid and docosahexaenoic acid) are discussed. Highly expressed miR-155 has been downregulated by flavonoids (through a quercetin-rich diet) and by vitamin D. Quercetin has been effective in modulating miR-146a. On the other hand, downregulated miR-125b expression was restored by vitamin D, Coenzyme Q10 and by microelement selenium. In conclusion, the miRNA profile, together with other 'omics', may constitute a multifaceted approach to explore the impact of diet on psoriasis prevention and treatment.